2021
DOI: 10.3389/fmolb.2021.761163
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram to Predict Tumor-Infiltrating Lymphocytes in Breast Cancer Patients

Abstract: Background: Tumor-infiltrating lymphocytes (TILs) play important roles in the prediction of prognosis and neoadjuvant therapy (NAT) efficacy in breast cancer (BRCA) patients, in this study, we identified clinicopathological factors related to BRCA TILs, then to construct and validate nomogram to predict high density of TILs.Methods: A total of 826 patients diagnosed with BRCA in Sun Yat-Sen University cancer center were enrolled in nomogram cohort. TILs were assessed using hematoxylin-eosin (H&E) stain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…By analyzing ER, PR, Ki67, and p53 as continuous variables, we were able to classify tumors into high- and low-expression diseases. Notably, the thresholds for ER, PR, Ki67, and p53 were determined based on ROC analysis rather than simply classifying them empirically as positive and negative; this differs from previous studies [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…By analyzing ER, PR, Ki67, and p53 as continuous variables, we were able to classify tumors into high- and low-expression diseases. Notably, the thresholds for ER, PR, Ki67, and p53 were determined based on ROC analysis rather than simply classifying them empirically as positive and negative; this differs from previous studies [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the prevalence of expression of TILs in our study was similar to some studies regardless of the cutoffs used, the prevalence reported varied significantly. [12–14] Previous studies reported a prevalence of expression of TILs of 26.5% to 44.5% using the 11% cutoff [15,16] and 5% to 26% using the 50% cutoff. [14,17,18] For example, in the Asian population, a study among 220 Korean participants with invasive breast cancer, this prevalence was 23.2% in biopsies and 27.6% in resected specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Through certain inflammasomes, pyroptosis is an inflammatory form of cell death triggered, which affects tumor proliferation, invasion, and metastasis under the regulation of some noncoding RNAs and other molecules. [ 27 ] Pyroptosis corresponds to an intensely inflammatory form of programmed cell death in which cytoplasmic contents and pro‐inflammatory cytokines, including IL‐1β, are released. [ 28 ] Doitsh et al [ 29 ] found that over 95% of quiescent lymphoid CD4 T cells die by caspase‐1‐mediated pyroptosis triggered by abortive viral infection in HIV‐infected hosts.…”
Section: Discussionmentioning
confidence: 99%